Morphometry of itaúba seedlings (Mezilaurus itauba (Meisn.) Taub. ex Mez) produced from alternative substrates (Research, Society and Development, 2021)
The use of alternative substrates can make economically viable the production of forest seedlings in nurseries, being also a sustainable alternative for agroforestry organic waste management. The species Mezilaurus itauba (Meisn.) Taub. ex Mez occurs in the Western Amazon, being a large tree with high economic potential, exploited by the timber sector. This work aimed to evaluate the effects of organic substrates on the production of itaúba seedlings. A completely randomized design was used, with four treatments: COCB - organic compost based on signal grass (1:1), SC - commercial substrate - SC, COCC - organic compost + chestnut husk (2:1) and COFC - organic compost + chestnut flour (2:1). The analysis of M. itauba seedlings was carried out using the following variables: shoot length - CPA, stem diameter - DC, ratio between shoot length and stem diameter - CPA/DC, root dry mass - MSR, aerial part - MSPA and total - MST and Dickson index – IQD. The seedlings produced in the substrate COCB (1:1) showed greater height, stem diameter and accumulation of root, shoot and total dry mass, resulting in a higher Dickson index value. Greater robustness was observed in seedlings produced in the COFC substrate. The commercial substrate originated seedlings with smaller height, diameter and less accumulation of root, shoot and total dry mass. The use of alternative substrates, such as organic compost, nut husk and flour, favors morphometric growth and biomass accumulation in M. itauba seedlings.